Copper-catalyzed selective C_O bond formation by oxidative α-C(sp3)_H/O_H coupling between ethers and salicylaldehydes. Issue 15 (15th April 2015) - Barve, Balaji D.; Wu, Yang-Chang; El-Shazly, Mohamed; Korinek, Michal; Cheng, Yuan-Bin; Wang, Jeh-Jeng; Chang, Fang-Rong
Abstract: Copper-catalyzed oxidative coupling of ethers and salicylaldehydes, via the direct α-C(sp 3 )–H bond functionalization of ethers in the presence tert -butyl hydroperoxide as an oxidant has been explored. The corresponding acetals were selectively formed in moderate to excellent yields. The sensitive formyl group of salicylaldehydes remained intact despite the oxidative reaction conditions. Graphical abstract: